Consumer's switching intention in crowdsourced delivery: a stimulus-organism-response perspective - Ng, Wei Hong (Nanyang Technological University, 2022)
This study examines customers’ switching intention in the Crowdsourced Delivery (CD) industry. Stimulus-Organism-Response (SOR) is used as an overarching framework for the theoretical model, with perceived value and perceived switching cost acting as mediators of switching intention. 500 respondents were collected from an online survey and structural equation modelling was then used to analyse the collected data. The results indicated that ease of use, breadth of use, and switching experience have notable direct effect on perceived switching cost. Whereas the constructs for social exchange theory (i.e., structural, financial, and social bonding strategies) have notable direct impact on perceived value. Finally, both perceived value and perceived switching have direct effect on consumers’ switching intention in the CD industry. By combining both perceived switching cost and perceived value in the theoretical model, 80.5% of the variance in CD users’ switching intentions can be explained. Additionally, results from the study can also aid CD service providers in developing suitable policies to retain their customers in a highly competitive environment.